New Approaches to Textual and Image Analysis in Early Jewish and Christian Studies - Schulthess, Sara,; Dilley, Paul,; Phillips, Peter,; Allen, Garrick V., (Digital Biblical Studies ;, 2022)
This volume explores Biblical Studies and its relationship to the Digital Humanities in all its complexity, focusing on new approaches to texts and images.